An examination of works by for wind band: Courage (March) by Harold Bennett/arr. Nicholas Contorno, Chasing Sunlight by Cait Nishimura, and Adrenaline Engines by Randall Standridge - Bazanos, Olivia Wei (Kansas State University, 2023)
The following report provides a comprehensive analysis of and teaching guide for works for wind band: Harold Bennett’s Courage (March), Cait Nishimura’s Chasing Sunlight, and Randall Standridge’s Adrenaline Engines. A chapter is included for each work, supplying essential information needed to properly prepare the conductor for teaching and rehearsing the work in question. The analytical methods employed in this document and the rehearsal techniques listed are based on the Blocker/Miles unit studies and macro-micro-macro concepts from the Teaching Music Through Performance in Band book series. Outlines of rehearsal plans used by the author are included with self-evaluations of each rehearsal, in addition to a detailed score analysis grid as presented by Dr. Frank Tracz in Mark Walker’s book, The Art of Interpretation of Band Music. Additionally, chapters are also devoted to the author’s philosophy of music education and philosophy of quality literature selection. All materials are included with the hope that this research can assist in preparation of these works by other conductors and ensembles, as well as to promote a more active programming of these quality, lesser-known works by composers.
Keywords: Music; Wind band; Nishimura; Standridge; Fillmore